Management of arbuscular mycorrhizal inoculation for the establishment, maintenance and recovery of grasslands - González, P. J.; Ramírez, J. F.; Rivera, R.; Hernández, A.; Plana, R.; Crespo, G.; Rosales, P. R. (Cuban Journal of Agricultural Science, 2016)
The inclusion of arbuscular mycorrhizal fungi (AMF) on fertilization systems for grasses and forage crops may be considered as an effective alternative to improve their productivity and nutritional value and, at the same time, to reduce the use of fertilizers. Starting from this condition, a research program was carried out for implementing an integral technology for the effective management of inoculation with AMF on these crops. This program included the selection of efficient strains of AMF, definition of mineral fertilizer dosages for establishment, maintenance and recovery of inoculated grasses, and determination of doses and frequency of inoculation for maintaining an effective mycorrhizal functioning of these crops. There was a high compatibility between the strain efficiency and type of soil on the response of grasses to inoculation with AMF. Type of soil, as well as grass species and its management, influenced on the permanence of the introduced strain, but, in all cases, inoculated grasses required lower doses of fertilizers than those with no inoculation, in order to reach adequate biomass yield and nutritional values. Inoculation with doses lower than 4x105 spores ha-1 of the efficient strain of AMF, every one or two years, depending on the duration of the effect of initial inoculation, guaranteed the permanence of an effective mycorrhizal functioning on established grasses. The introduction, at production scale, of fertilization systems, based on the inoculation of an effective strain of AMF and the application of complementary levels of mineral or organic fertilizers, contributed to save up to 50% of fertilizer doses recommended for these crops, without reducing yield or nutritional value of biomass. Key words: mycorrhizae, mineral fertilization, organic fertilization, grasses